Personal Branding Pimpinan SD Islam Al Ikhlas Dalam Mempertahankan Citra Sekolah - Putri, Alantika; Yuniani, Hani; Meliala, Robbikal Muntaha (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The purpose of this study is to see how the Personal Branding of the Principals of Al Ikhlas Islamic Elementary School maintains the school's image. This study will focus on the Personal Branding of the Principals of Al Ikhlas Islamic Elementary School starting from the Vice Principal to the Principal. A qualitative approach is used through interviews and holding group discussion forums with four participants who are the leaders mentioned above. Data analysis was carried out using a thematic approach to identify patterns in the Personal Branding strategies used, challenges faced, and strategies to maintain the integrity of the school's image. The results of the study show that the Principals of Al Ikhlas Islamic Elementary School in maintaining the school's image, consistently convey the advantages of policies by using open communication. As a form of education for teachers and employees so that the cons or issues that occur do not continue into a crisis.